The poisoned chocolates case - Berkeley, Anthony, 1893-1971 (House of Stratus, 2001)
In this, the best-known of Anthony Berkeley's novels, amateur detective Roger Sheringham investigates his most famous case. When Joan Bendix makes a bet with her husband for a box of chocolates, no one imagines that winning will cost her her life. The seven she eats poison her and the two her husband eats nearly kill him. The Sheringham Crime Circle find the unusual case baffling, but eventually come up with some very interesting theories - which they then proceed to disprove one by one. Due to a series of false clues the identity - and motive - of the killer appears to be out of reach... AUTHBIO: A journalist as well as a novelist, Anthony Berkeley was a founding member of the Detection Club and one of crime fiction's greatest innovators. He was one of the first to predict the development of the 'psychological' crime novel and he sometimes wrote under the pseudonym of Francis Iles. He wrote twenty-four novels, ten of which feature his amateur detective, Roger Sheringham